1, 25(OH)2D3 attenuates hepatic steatosis by inducing autophagy in mice. Issue 3 (1st February 2017) - Li, Renlong; Guo, Enshuang; Yang, Jiankun; Li, Anyi; Yang, Yan; Liu, Shenpei; Liu, Anding; Jiang, Xiaojing
Abstract : Objective: 1, 25(OH)2 D3 has been reported to attenuate liver steatosis; however, its exact mechanism of action remains poorly understood. This study aimed to determine whether 1, 25(OH)2 D3 can attenuate hepatic steatosis by inducing autophagy. Methods: Male C57BL/6 mice fed a high‐fat diet (HFD) were injected with 1, 25(OH)2 D3 for 4 weeks. These mice were given 3‐methyladenine (3‐MA) to inhibit autophagy. HepG2 cells were preincubated with a free fatty acid (FFA) and then treated with 1, 25(OH)2 D3 . Vitamin D receptor (VDR) shRNA and autophagy‐related 16‐like 1 (ATG16L1) siRNA were used for VDR knockdown or ATG16L1 silencing, respectively. Results: 1, 25(OH)2 D3 diminished HFD‐induced liver damage and steatosis, changes accompanied by autophagy and ATG16L1 expression upregulation. Inhibition of 1, 25(OH)2 D3 ‐induced autophagy mediated by 3‐MA blocked the protective effects of 1, 25(OH)2 D3 on hepatic steatosis. Additionally, 1, 25(OH)2 D3 ‐induced autophagy appeared to play a role in anti‐inflammation and lipid metabolism modulation in the liver. In HepG2 cells, 1, 25(OH)2 D3 reduced lipid accumulation and increased autophagy and ATG16L1 expression; however, this effect was abrogated after VDR knockdown. The protective effects of 1, 25(OH)2 D3 ‐mediated autophagy against lipid accumulation were abolished by 3‐MA. Furthermore, siRNA‐mediated ATG16L1 knockdown prevented 1, 25(OH)2 D3 ‐induced autophagy, resulting in increased fat accumulation. Conclusions: The data suggest that 1, 25(OH)2 D3 may ameliorate hepatic steatosis by inducing autophagy by upregulating ATG16L1.